MANAJEMEN KEAMANAN CYBER DI ERA DIGITAL - Susanto, Edy; Antira, Lady; Kevin, Kevin; Stanzah, Edo; Majid, Assyeh Annasrul (Journal of Business And Entrepreneurship, 2023)
In this rapidly growing digital era, cyber security has become one of the most important aspects to pay attention to. Technological development information and communication has provided many benefits to our lives, they also present serious risks related to data security.. Cyber can be in the form of data theft, destruction systems, manipulation of information, or identity theft. First, cyberattacks are getting more complex and constantly evolving with time technology advances. Attackers can variety of methods and tools sophisticated way to exploit system vulnerabilities and gain access invalid. Second, cyber are often cross-border in nature, where attackers can operate overseas making difficult to identify and law enforcement. In addition, technological advances have also expanded attacks into new domains, such as the Internet of Things (IoT), autonomous vehicle systems, and artificial intelligence. Expanding connectivity between devices and internet-connected infrastructure increases security complexity cyber. However, it is important to remember that cyber security is not a challenge can't be overcome. In an effort to protect data and computer systems using various security strategies and measures can be implemented. With a combination of technical approaches, strong security policies, training user awareness, and cooperation between the parties involved, security cyber can be significantly improved.